Nacjonalizm a uniwersalne wartości. Spór o tożsamość z perspektywy ﬁlozoﬁi dialogu - Rebes, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In this chapter I deal with the problem of contemporary nationalism through the prism of the philosophy of dialogue and the question about the identity of the individual and society.The chapter consists of three parts. Firstly, I conceptualise the notions of nationalism and nation states. Secondly, I present the assumptions of the philosophy of dialogue concerning the problem of identity and the source relationship in philosophy. Thirdly and lastly, I analyse how nationalism is juxtaposed with the universal values as set against the background of the philosophy of dialogue.Here I do not focus on presenting the deﬁnition or assessment of nationalism. I oﬀer instead an insight on some elements that appear particularly strong in the initial phase of the transformation of nationalism in nation-states, which lead to various kinds of dangerous phenomena, and present the problem of nationalism through the prism of national socialism. The phenomenon of nationalism, for which the uniqueness of a nation is one of the most characteristic features, may pose a serious problem not only in international or social relations, but also concerns individuals. The philosophy of dialogue is involved in ethical relations between individuals, but its scope also extends to social and even political issues. Representatives of the philosophy of dialogue noticed the problem of culture grounded in the question of the subject before it led to the drama of the citizens of Europe and, consequently, of the whole world. Therefore, the article juxtaposes nationalism with the postulates of the philosophy of dialogue, which shows identity through the prism of a relationship to another human being.I consider this problem on the basis of philosophical anthropology. For this purpose, a phenomenological reﬂection was used, which consists in describing the phenomenon and trying to understand it through the prism of “I”. The reason why the philosophy of Hegel, Schopenhauer, and Nietzsche inspires, on the one hand, National Socialism, and on the other, the philosophy of dialogue, is shown. This particular task is to help understand today’s problems of nation-states seeking their own identity. The common denominator of these two separate phenomena is the problem of identity.The problem of symmetry and asymmetry of relations or the problem of violence and being for the other in the concept of the national idea and the philosophy of dialogue is presented. They can be seen through the prism of the question of identity. On the one hand, nationalism is based on universalism, and on the other, it seeks uniqueness, a unique place for its nation. It is clearly in contradiction to universal values which are the same for all. The dispute over identity from the perspective of the philosophy of dialogue touches upon an important issue, which is the importance of the Other for identity. The philosophies of Kant, Hegel, or Nietzsche, when misunderstood, may lead to the conclusion that they are the precursors of nationalism, including National Socialism. However, this is a great misconception. The philosophy of dialogue critically evaluates these thinkers, but they give it a reason to reﬂect on the essence, on the root question of philosophy.The philosophy of dialogue teaches that individual experience can be universal, without excluding others. This helps to see the necessary balance between the identity of the individual and the national identity that need each other. National identity is a very important element of human nature, but it must be based on symmetry in interpersonal relations, which can guarantee peace in Europe and the world.
Keywords: nacjonalizm; ﬁlozoﬁa dialogu; Ja; Inny